A regulamentação do Sistema Financeiro e o mercado OTC: uma análise da capacidade de impedir novas crises - Silveira, Marina Fernandes da (2019)
The impacts of the 2007/2008 financial crisis that has crashed the world’s economies are still felt. Many studies have focused on their main causes, among them derivatives traded in over the counter (OTC) markets. OTC derivatives are bilateral trading, with exposures do not known by the Market and not guaranteed by clearing houses. The derivative’s Market growth was extremely expressive in the 21st century, mainly of credit derivatives. Due to this reason, the purpose is to analyze the initiatives of financial sector regulations through the Bank for International Settlements (BIS) mostly after Basel III published after the financial crisis. The study adopts literature reviews of norms published by BIS under the responsibility of Banking Supervision Committee of Basel, as well as BIS statistical data is used to analyze the evolution of the market size of OTC derivatives before and after of the crisis. Moreover, other literatures are used to support the criticism of proposed study about insufficient to inhibit the OTC derivatives market and avoid a new crisis. Despite the recent regulation proposed by BIS to regulate OTC derivative products, it is deduced that they are not able to inhibit their negotiations, only mitigate their risk. The conclusion is these new regulations are incapable of preventing a new crisis of this nature, but probably it will not happen in the same proportion